EFEKTIVITAS PERMA NOMOR 1 TAHUN 2013 DALAM PENANGANAN HARTA KEKAYAAN TINDAK PIDANA PENCUCIAN UANG OLEH PENYIDIK SUBDIT III DITTIPIDEKSUS BARESKRIM POLRI - Syarlis; M. Mustofa; Novi Indah Earlyanti (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effectiveness of the implementation of Supreme Court Regulation (PERMA) Number 1 of 2013 in the application for handling assets derived from money laundering crimes by investigators of Sub-Directorate III of the Directorate of Special Economic Crimes (Dittipideksus) at the Criminal Investigation Department (Bareskrim) of the Indonesian National Police. PERMA serves as an alternative procedural mechanism when the suspect is not found, complementing the limitations of the Criminal Procedure Code (KUHAP) and filling the procedural legal void referred to in Article 67 paragraph (2) of Law Number 8 of 2010. This research also aims to identify the obstacles faced by investigators and analyze the solutions applied by investigators to overcome those obstacles. The study employs a constructivist paradigm with a qualitative approach using field research methods. Data collection techniques include interviews, observations, and document studies. The validity of the data is tested using source, method, and time triangulation techniques. Data analysis follows the Miles & Huberman model, which consists of data reduction, data presentation, and conclusion drawing. The results show that the application of PERMA is relatively effective in providing legal certainty over assets derived from money laundering crimes where suspects remain unidentified during investigation. The stages of the application process include the receipt of an Analysis Report (LHA) from the Financial Transaction Reports and Analysis Center (PPATK), investigation, prosecution, submission of case files, and filing of asset handling requests to the District Court where the assets are located. The obstacles found in the implementation of PERMA include: limited scope of assets eligible for application, strict procedural deadlines, differences in legal interpretation between investigators and judges, weak inter-agency coordination, and low levels of public socialization resulting in negative perceptions. To overcome these challenges, investigators implement various solutions such as: discretionary urgent seizures, accelerated asset seizure processes, intensive public outreach on the applicable regulations, streamlined inter-agency coordination, and improved investigator competence. These solutions reflect a responsive and adaptive law enforcement approach in the context of state asset recovery.